Hubungan Anak Wasting dengan Penyakit Infeksi Saluran Pernapasan Akut di Kota Salatiga - Renyoet, Brigitte Sarah; Mebang, Ryska Stephani; Fretes, Fiane de (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Wasting is a group of acute nutritional deficiencies that can increase the risk of infectious diseases, one of which is Acute Respiratory Infection (ARI). Salatiga City is one of the cities in Central Java Province that has ARI cases, which is around 7.78% in 2018. this research purposed to find the relationship between wasting children with Infectious Disease in Salatiga.Methods: The Quantitative research method with univariate and bivariate analysis using Spearman Rho correlation test.Result: The results of the study in 4 sub-districts of Salatiga City obtained 36 children aged 36-59 who had wasting and had a history or were experiencing ARI. The main variables are wasting children and ARI did not have a significant relationship p> 0.050 and supporting factors included BCG immunization, exclusive breastfeeding status, complementary feeding status, parental knowledge, air pollution, environmental sanitation, and personal hygiene showed no relationship between wasting children who had a history of or were experiencing ARI p> 0.050.Conclusion : The conclusion is obtained between the main variables and supporting factors, no significant results were found and it is recommended for parents of children to pay attention to food intake, hygiene, and routinely participate in posyandu activities. The next recommendation is that this research can be developed both in terms of method design and a larger number of samples, as well as other supporting factors that can affect children experiencing wasting and ARI.